STUDI DESKRIPTIF PROKRASTINASI AKADEMIK SISWA - Dindin Kurniadin; Nandang Rukanda; Rima Irmayanti (IKIP Siliwangi, 2023)
Student academic procrastination is a behavior of procrastinating that is intentionally repetitive and prefers to fill its activities by doing more enjoyable activities so that it overrides its main task as a student.This study aims to describe the academic procrastination of high school students Al Amanah Ciwidey class XI, this study uses a quantitative descriptive method.The subjects in this study were students of class XI SMA Al Amanah Ciwidey. The results of this study indicate that the level of academic procrastination of students both overall and by gender is in the moderate category.which means that class XI students of SMA Al Amanah Ciwidey are expected to be able to overcome the problem of academic procrastination. Keywords:Student Academic Procrastination, High school student.